2020
DOI: 10.1186/s13046-020-01641-8
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia induced ferritin light chain (FTL) promoted epithelia mesenchymal transition and chemoresistance of glioma

Abstract: Background Hypoxia, a fundamental characteristic of glioma, is considered to promote tumor malignancy by inducing process of epithelial mesenchymal transition (EMT). Ferritin Light Chain (FTL) is one of the iron metabolism regulators and is overexpressed in glioma. However, relationship between hypoxia and FTL expression and its role in regulating EMT remains unclear. Methods Immunohistochemistry (IHC), western blot and public datasets were used to evaluate FTL level in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 39 publications
0
71
0
1
Order By: Relevance
“…Ferritin, the most important iron storage form in humans, is an essential nutrient that plays crucial roles in diverse cellular physiopathological processes, including regulation of the tumor microenvironment and immunometabolism [ 1 , 2 ]. Ferritin is composed of two subunits: a light chain (FTL, 19 kDa) and a heavy chain (FTH, 21 kDa) [ 3 ]. We previously showed that FTH1 and FTL have positive linear correlation and the protein expression levels of both were higher in head and neck squamous cell carcinoma (HNSC) tumor tissues compared with normal tissues, and that elevated FTH1 was related to poorer prognosis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ferritin, the most important iron storage form in humans, is an essential nutrient that plays crucial roles in diverse cellular physiopathological processes, including regulation of the tumor microenvironment and immunometabolism [ 1 , 2 ]. Ferritin is composed of two subunits: a light chain (FTL, 19 kDa) and a heavy chain (FTH, 21 kDa) [ 3 ]. We previously showed that FTH1 and FTL have positive linear correlation and the protein expression levels of both were higher in head and neck squamous cell carcinoma (HNSC) tumor tissues compared with normal tissues, and that elevated FTH1 was related to poorer prognosis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Correlation analysis of clinical samples shown that miR-137 was positively correlated with E-cadherin, and contrary to Vimentin, indicating that miR-137 may promote TMZ sensitivity by affecting EMT-related factors. Accumulating evidence showed that Wnt/bcatenin pathway played crucial role in regulating EMT (35)(36)(37). Wnt/b-catenin pathway involves the stabilization of b-catenin through the binding of Wnt ligand to cell surface receptors such as LRP6.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that hypoxic tumors have a poor vascularization that limits drug bioavailability [ 91 ]. In addition, the low O 2 tension reduces the possibility of inducing oxidative stress that is often a mechanism of killing exerted by chemotherapeutic drugs [ 36 ], such as cisplatin [ 92 ], doxorubicin, etoposide [ 93 ], gemcitabine [ 94 ]. Moreover, by creating an unfavorable environment, hypoxia selects aggressive and metastatic clones, as well as clones rich of anti-apoptotic proteins such as IAP3 and Bcl-2: this selection is independent on HIF-1ɑ activation [ 95 ], but it contributes to counteract the apoptosis induced by anti-cancer agents.…”
Section: Hypoxia and Altered Upr: Two Partners In Crime Of Chemoresismentioning
confidence: 99%
“…Finally, HIF-1α increases resistance to chemotherapy by promoting EMT [ 36 ], which induces cell proliferation and migration, as demontstrated by the down-regulation of E-cadherin and the up-regulation of vimentin in hypoxic PC cells. Propofol, recently identified as a HIF-1α inhibitor, not only reduces EMT but also sensitizes cells to docetaxel [ 146 ].…”
Section: Hypoxia and Altered Upr: Two Partners In Crime Of Chemoresismentioning
confidence: 99%
See 1 more Smart Citation